Colonization of Pseudomonas aeruginosa CR56 in the rhizosphere of cucumber and tomato - LOU Bing-gan; ZHANG Bing-xin; Maarten Ryder (浙江大学学报. 农业与生命科学版, 2001)
Pseudomonas aeruginosa strain CR56 is effective to control cucumber and tomato seedlings damping-off disease caused by Pythium spp. and Rhizoctonia solania as a seed treatment. A strain resistant to rifampin, CR56R9, and a lacZY-marked derivative of wild strain CR56, CR56RL4, which were used to study the colonization ability, fluctuation of populations and distribution pattern on the rhizosphere of cucumber and tomato. The studies indicated the rhizosphere of cucumber was more suitable for the strains CR56R9 and CR56RL4 to colonize than the rhizosphere of tomato. The fluctuation of the two strains population was declined more quickly in the rhizosphere of tomato than that of cucumber. For 28 days after planting, the populations of CR56R9 and CR56RL4 in the rhizosphere of cucumber were declined from inoculum level 7.63×107 and 4.88×107 CFU per seed to 9.85×106 and 8.87×106 CFU per plant, respectively, and the populations in the rhizosphere of tomato were declined from inoculum level 3.0 × 107 and 2.13 × 107 CFU per seed to 4.48 × 105 and 4.37 × 105 CFU per plant. The fluctuation of the introduced bacteria population was declined more quickly in the rhizosphere of tomato than of cucumber. It was found that the introduced bacteria were mainly in the location where damping-off disease occurred, namely in the base of roots. The introduced bacteria weren't detected in the tip of root. The living ability in the rhizosphere of cucumber and tomato between a lacZY gene marked strain and a rifampin-resistant strain was very similar.